Kepurusa as a Women’s Inheritance System in Bali: Dynamics of Customary, National, and Islamic Law - Abdussalam, Izuddin; Beatricia, Ezraella Geraldine; Nurinsan, Sania Raisyabila; Atikah, Rana; Shouniah, Gita (El-Usrah: Jurnal Hukum Keluarga, 2026)
The legal system currently in force is inseparable from its long historical development. It is deeply-rooted in the spirit and identity of the nation, as well as in both Islamic law and customary law, for therein lies the true identity of Indonesian law. In Balinese customary law communities, inheritance distribution is based on a patrilineal system. Inheritance is granted to male descendants within the family, and a distinguishing feature in Balinese customary law is the principle of sentana rajeg (a daughter granted patrilineal heir status). This refers to a condition in which, when an heir has only daughters, a daughter may enter into a marriage in which the husband is incorporated into her family. This incorporation subsequently creates predana status. This study employs a normative juridical research method, analyzed through the theory of Islamic law. Data collection was conducted through library research. In the case being studied, inheritance of land was instead granted to a person who was neither part of the family bond nor held predana status. Although traditionally adhering to the Kepurusa system, developments in law and jurisprudence (e.g., Supreme Court Decision Number 1331 K/Pdt/2010) indicate that the concepts of Islamic inheritance law and Balinese customary law are alternative yet aligned, which is in accordance with the principle of justice. Another finding is the adjustment made to accommodate inheritance rights for daughters under certain criteria (e.g., not marrying outside the family, caring for parents, or based on family/customary agreements) in order to achieve the values of justice and equality.